Higher education in Iraq : its process and features of development during the period of 1932 A.D – 1958 A.D (Journal Of Educational and Psychological Researches, 2015)
In order to specify the features of higher education process and its quantitative and qualitative development in Iraq ; one should look back at its historical process and the need of interesting with it .Accordingly , there will be a chance for verifying the demand of the Iraqi society according to the political , social , and cultural changes especially  during the national governance (1932 – 1958 ) .For depicting the most important quantitative and qualitative development of this kind of education the period of 1932 -1958 , and since there is no previous study that tackled this topic , here comes the need of writing this paper .After historical and descriptive analysis of the data and the information supported by the references and the books , the paper concluded the following : • During this period , higher education in Iraq had witnessed the development of several colleges like college of economy and trade 1936  , college of pharmacy 1938 ,college of arts and sciences 1949 ,guiding college 1948, college of agricultural 1950 ,college of dentistry 1953 , college of veterinary medicine 1955 .• Many schools and higher institutes where also established like : college of domestic arts 1932 – 1933 , institutes of fine arts 1936 , institute of Queen Alyaa 1945 , the higher institute of industrial engineering 1950 , the higher institute of physical education 1954. • Sevral college and institutes had also been reopened and the developed . those which already existed in 1932 like : law school 1908 , college of sharia 1912,college of engineering 1917 , higher academy of teachers 1923 ,college of medicine 1927 .• That historical period of the higher education development had also witnessed a quantitative and qualitative growth in preparing students ( males – females ) and instructors in the higher institutes and college , in addition to the growth of quality and the quantity of students missions from Iraq and the other Arabic countries . • That period had also involved the establishment of the first Iraqi University called University of Baghdad.• Several committees had been formed in that period .they discussed the importance of opening several colleges and concentrated on the curricula taught there . they also discussed the means of putting criteria of students acceptance in the college and institutes .